Application of design thinking technologies in the development of authorial textures for contemporary fashion - Hryhorova, larysa; Kuratova, Maria (Professional Art Education, 2025)
The article examines current issues related to the development and implementation of design concepts based on design thinking methodology, digital design technologies, and the collection and analysis of data on signature textures. The stages of design thinking for the creation of fashion items are analyzed, in which texture becomes one of the main means of artistic expression, most clearly reflecting the features of structure and surface decoration as well as the uniqueness of artistic technique. A classification of textures is proposed, with particular attention paid to the aesthetic and utilitarian functions of surfaces. To understand how texture serves as a means of shaping costume imagery in fashion design, the main types of textures are described and the methods of using textures in clothing composition are defined. It is established that texture not only serves a technical function but also represents the signature of a designer’s individual style. Texture – the surface of the form –creates the external appearance of the product and defines its visual image. Based on the analysis, a collection of contemporary clothing using signature textures and design thinking practices has been developed.
Keywords: Design thinking; arment design; fashion product; signature surface textures; compositional structure; fabric texture; creative development; design; artistic form formation